A Christmas resolution : a novel - Perry, Anne (Perry, Anne. Christmas novels, 2020)
"When Celia Hooper discovers that her dear friend Clementine is to marry widower Seth Marlowe - a man with a sinister past - she calls upon her husband, Detective John Hooper of the Thames River Police, to help her find out what really happened to Seth's first wife several years ago. Rumour has it that she killed herself and Seth's daughter ran away to live on the streets but no one seems to know the truth."--Provided by publisher